Male medaka continue to mate with females despite sperm depletion - Yuki Kondo; Masanori Kohda; Satoshi Awata (Royal Society Open Science)
In animals where males engage in multiple matings, sperm depletion can substantially reduce the reproductive success of both sexes. However, little is known about how successive matings affect sperm depletion, fertilization rates and mating behaviour. Here, we investigated this phenomenon under laboratory conditions. Medaka (Oryzias latipes), an externally fertilizing fish, is an ideal model to test predictions of sperm depletion because there are established methods to observe its mating and count sperm. Medaka males mated with multiple females (19 per day, on average; range, 4–27), experiencing significant sperm depletion, with sperm release declining markedly after the first few matings, reaching only 0.5–6.3% by the last mating of the day. Fertilization rates decreased, particularly after approximately 10 consecutive matings, although there was some recovery in the next-day’s matings. The decline in courtship effort and mating duration probably resulted from the males becoming increasingly fatigued. Despite the reduced sperm availability, females did not adjust their clutch size as a counterstrategy. These results suggest substantial reproductive costs for males and the potential for sexual conflict owing to limited sperm availability. For species with frequent successive mating, these findings highlight the need to reconsider reproductive strategies and their impact on sexual selection.